2019
DOI: 10.1186/s40645-019-0268-z
|View full text |Cite
|
Sign up to set email alerts
|

In situ investigation of stone heritage sites for conservation purposes: a case study of the Székesfehérvár Ruin Garden in Hungary

Abstract: This paper demonstrates the application of in situ diagnostic tools to document stone heritage sites prior to conservation interventions using a Medieval ruin of Central Europe (Székesfehérvár, Hungary). The applied methods included lithological mapping and characterisation and mapping of decay forms as well as in situ measurements of physical parameters such as Schmidt hammer rebound, moisture content and micro-drilling resistance. The combination of these methods allowed the condition assessment of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Conservation of architectural heritage is preceded by proper assessment of its structural elements and material to determine the causes of decay and its degree as well as the appropriate conservation measure to be applied [10,29]. The preliminary assessment is done by visual observation, by which conservators and architects evaluate decay only with naked eyes without any instrument.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation of architectural heritage is preceded by proper assessment of its structural elements and material to determine the causes of decay and its degree as well as the appropriate conservation measure to be applied [10,29]. The preliminary assessment is done by visual observation, by which conservators and architects evaluate decay only with naked eyes without any instrument.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Despite this approach, the use of innovative methods is lacking in various conservation management plans for architectural heritage in Nigeria. Studies [9][10][11] have shown that the holistic use of innovative technologies as a complement to the traditional conventional methods boosts the efficacy of both methods for conservation purposes. The benefits of the proper application of traditional conventional methods lie in the principle of using materials that are of the same type as the deteriorated ones during conservation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Characterisation of representative walls is fundamental to understanding the structural behaviour of a wall (Theodoridou and Török, 2019). Coursed rubble is the cheapest and roughest type of stone masonry.…”
Section: Thermal and Hydric Dilatometrymentioning
confidence: 99%
“…or extrinsic factors of decay (microclimatic conditions such as temperature and humidity changes, water/moisture transportation, air pollution, biological activities, etc. ), enable planning the most appropriate strategies needed to reduce weathering of stone [ 18 , 19 , 20 ]. The conservation of historic and culturally relevant stone artworks and buildings involves the on-site protection and/or restoration, usually achieved by re-establishing grain-to-grain cohesion of damaged stone through the application of organic polymers, alkoxysilanes or inorganic consolidant compounds [ 15 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%